A protocol for Agrobacterium-mediated transformation of banana with a rice chitinase gene. - Sreeramanan, S.; Mahmood, Maziah; Xavier, R. (United Arab Emirates University, 2009)
A rice chitinase gene (RCC2) multiplied in Agrobacterium strain (EHA 101), was simultaneously introduced into single buds of in vitro grown banana cultivar, Rastali (AAB). Plasmid pBI333-EN4-RCC2 contained a hygromycin phosphotransferase gene (hptII) as the selectable marker and gusA gene as a reporter marker to identify the transformants.. Single buds derived from multiple bud clumps (Mbcs), were the target explants for transformation. Transformation frequency based on hygromycin selection (25 mg L-1) was higher, although no positive transformant was confirmed based on PCR and Southern blot analyses.. Stable gusA gene expression was detectable in transformed single buds, multiple bud clumps, shoots, leaves and roots derived from hygromycin selection at 50 mg L-1 ). An assay was performed to identify the minimum concentration of two antibiotics most effective against Agrobacterium EHA 101. Protein assay showed an increase in chitinase enzyme activity of transformed plantlets. The Agrobacterium-mediated transformation protocol reported here is suitable for future selection of banana meristem tissues resistant to fungal disease.